Tectonothermal evolution of the Lohit Valley, Eastern Himalaya: New low‐temperature thermochronological constraints. Issue 2 (19th January 2022) - Mukherjee, Kunal; Adlakha, Vikas; Banerjee, Sayandeep; Sen, Koushik
Abstract : The present contribution provides the first low‐temperature thermochronological record from the Lohit Valley, Eastern Himalaya, presenting eight ZHe and two AHe cooling ages across the major tectonic boundaries. The ZHe cooling ages range from 6.94 ± 1.17 Ma to 12.51 ± 2.84 Ma, whereas AHe ages vary between 1.73 ± 0.15 Ma and 3.56 ± 0.42 Ma. The ZHe cooling ages suggest that the Mishmi Crystallines exposed at the southwestern mountain front are the slowest exhuming domain since ~12 Ma. The ZHe ages are youngest in the Demwe Thrust (DT) zone, and the contact between the frontal low‐grade metamorphic rocks of Mishmi Crystalline and high‐grade gneissic rocks of the Mayodia Group. The rapid exhumation in the DT zone as obtained from the ZHe cooling ages suggests an out‐of‐sequence thrusting at ~7 Ma. The QTQt thermal history modelling of the co‐genetic pairs of ZHe and AHe cooling ages of the northeasternmost Lohit Plutonic Complex suggests that the exhumation rates in this region were as high as ~3.7 mm/year during the Pliocene‐Quaternary. These high exhumation rates are in good correlation with the local topographic relief, hill slopes, and channel steepness, which suggests the establishment of the present‐day topography of the Lohit valley region at the latest by Pliocene‐Quaternary. Variation in exhumation rates does not correlate with the present‐day precipitation pattern. Tectonics appears to be the prime driver for exhumation rates of the Lohit valley region of the easternmost Himalaya. Abstract : This paper provides the first thermochronological record of lithounits from Lohit Valley, Arunachal Himalaya, NE India, and reveals the activity along Demwe Thrust (DT) from ~6 to 8 Ma. Thermal history modelling of co‐genetic pair of zircon He and apatite He cooling ages along the Walong Thrust (WT) in the eastern Lohit Plutonic complex (LPC) suggests rapid cooling from ~3.6 to 2.5 Ma as shown in the graphical abstract. We interpret this rapid cooling as activity along the WT in this region during Plio‐Quaternary.